A high-hardness, anti-aging, anti-corrosion self-cleaning coating and a preparation method thereof

CN122917645APending Publication Date: 2026-10-16CHANGSHA MINDE FIRE ENG PAINT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611363129.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

该制备方法简单,所得复合材料附着力强,透明,光响应范围广,催化活性高,但其抗老化性能、抗腐蚀性能仍有不足

Benefits of technology

本发明制备的自清洁涂料具有较高的硬度以及优异的抗老化性能、耐腐蚀性能和自清洁性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917645A_ABST
    Figure CN122917645A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high hardness, anti-aging, corrosion-resistant self-cleaning paint and preparation method thereof, and relates to the field of paint technology.The high hardness, anti-aging, corrosion-resistant self-cleaning paint includes the following raw materials by weight fraction: epoxy resin 25-40 parts, polyurethane resin 20-30 parts, fluorocarbon resin 8-15 parts, nano zirconium oxide 2-3 parts, nano silicon dioxide 1-2 parts, nano titanium dioxide 3-5 parts, hydrophobic fumed white carbon black 0.5-2 parts, corrosion inhibitor 1-2 parts, anti-aging agent 1-3 parts, leveling agent 0.5-2 parts, dispersing agent 0.5-2 parts, curing agent 10-15 parts, organic solvent 40-60 parts.The self-cleaning paint prepared by the application has high hardness and excellent anti-aging performance, corrosion resistance and self-cleaning performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fluorocarbon resin coating technology, specifically to a high-hardness, anti-aging, and anti-corrosion self-cleaning coating and its preparation method. Background Technology

[0002] As an important material in modern industry and construction, coatings face increasingly stringent performance requirements. Particularly in architectural decoration, industrial protection, and electronic equipment, higher demands are placed on coatings' hardness, gloss, weather resistance, corrosion resistance, and self-cleaning capabilities. While traditional coating products are relatively mature in terms of single functions, they still have shortcomings in multi-functional integration. Existing technologies generally suffer from problems such as the contradiction between coating hardness and flexibility, limited self-cleaning function, poor anti-aging properties, and insufficient corrosion resistance.

[0003] Chinese invention patent CN109608913A discloses a Pt-TiO2-SiO2 photocatalytic self-cleaning composite material and its preparation method. The method involves mixing a mixed solution of oxalic acid, water, anhydrous ethanol, and hydroxyl-terminated polydimethylsiloxane, a mixed solution of isopropyl titanate, chloroplatinic acid solution, and anhydrous ethanol, with tetraethyl silicate. A subsequent reaction under ultraviolet light irradiation yields the photocatalytic self-cleaning composite material. Using oxalic acid as a catalyst and chelating agent, highly active anatase-phase titanium dioxide can be prepared without calcination, resulting in a homogeneous sol. Hydroxyl-terminated polydimethylsiloxane is used as an organic additive to obtain a structurally stable, hydrophobic, and self-cleaning organic-inorganic composite material. A photoreduction method is employed to reduce platinum ions and load them onto the titanium dioxide surface. This preparation method is simple, and the resulting composite material exhibits strong adhesion, transparency, a wide light response range, and high catalytic activity. However, its anti-aging and anti-corrosion properties are still insufficient.

[0004] Therefore, it is of great significance to develop a self-cleaning coating with multiple functions such as high hardness, anti-aging, and anti-corrosion. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a self-cleaning coating with high hardness, anti-aging and anti-corrosion properties and its preparation method.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A self-cleaning coating with high hardness, anti-aging, and corrosion resistance, comprising the following raw materials in parts by weight: Epoxy resin 25-40 parts, polyurethane resin 20-30 parts, fluorocarbon resin 8-15 parts, nano zirconium oxide 2-3 parts, nano silica 1-2 parts, nano titanium dioxide 3-5 parts, hydrophobic fumed silica 0.5-2 parts, corrosion resistant agent 1-2 parts, anti-aging agent 1-3 parts, leveling agent 0.5-2 parts, dispersant 0.5-2 parts, curing agent 10-15 parts, organic solvent 40-60 parts; The corrosion resistant agent is prepared by the following method: S1: 1,3-Benzothiazol-5-amine reacts with diethyl 2,3-epoxypropylphosphonate to generate intermediate 1, as shown in the following schematic equation:

[0007] S2: Intermediate 1 reacts with 2-imidazolidineone-4-carboxylic acid to form a corrosion resistant agent. The reaction equation is shown below:

[0008] In step S1, the molar ratio of 1,3-benzothiazole-5-amine to diethyl 2,3-epoxypropylphosphonate is 1:(2.01-2.03).

[0009] In step S2, the molar ratio of intermediate 1 to 2-imidazolidineone-4-carboxylic acid is 1:(2.05-2.1).

[0010] The anti-aging agent is prepared by the following method: N1: N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine reacts with 1,2-epoxydodecane to generate intermediate A, as shown in the following schematic equation:

[0011] N2: Tripropylene phosphite reacts with 2-(2-mercaptoethyl)-1H-benzimidazole-5-carboxylic acid to generate intermediate B, as shown in the following schematic equation:

[0012] N3: Intermediate B reacts with intermediate A to form an anti-aging agent. The reaction equation is shown below:

[0013] In step N1, the molar ratio of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine to 1,2-epoxydodecane is 1:1.02.

[0014] In step N2, the molar ratio of tripropylene phosphite to 2-(2-mercaptoethyl)-1H-benzimidazole-5-carboxylic acid is 1:3.05.

[0015] In step N3, the molar ratio of intermediate B to intermediate A is 1:3.1.

[0016] A method for preparing a self-cleaning coating with high hardness, anti-aging, and corrosion resistance includes the following steps: (1) Weigh the following by weight: 25-40 parts epoxy resin, 20-30 parts polyurethane resin, 8-15 parts fluorocarbon resin, 2-3 parts nano zirconium oxide, 1-2 parts nano silica, 3-5 parts nano titanium dioxide, 0.5-2 parts hydrophobic fumed silica, 1-2 parts corrosion resistant agent, 1-3 parts anti-aging agent, 0.5-2 parts leveling agent, 0.5-2 parts dispersant, 10-15 parts curing agent, and 40-60 parts organic solvent; (2) Disperse organic solvent, nano zirconium oxide and nano silica evenly, add nano titanium dioxide and hydrophobic fumed silica, continue to disperse evenly to obtain slurry, grind the slurry to obtain pre-dispersed filler system; mix epoxy resin, polyurethane resin and fluorocarbon resin, heat and stir, then add corrosion resistant agent, anti-aging agent, leveling agent, dispersant and pre-dispersed filler system in sequence, stir and mix evenly, cool down, add curing agent, stir, sieve and mature to obtain high hardness, anti-aging and anti-corrosion self-cleaning coating.

[0017] Due to the adoption of the above technical solutions, the beneficial effects of the present invention include: The self-cleaning coating prepared by this invention has high hardness and excellent anti-aging, corrosion resistance and self-cleaning properties. Attached Figure Description

[0018] Figure 1 The photon nuclear magnetic resonance (NMR) spectrum of the corrosion resistant agent prepared in Example 1 is shown.

[0019] Figure 2 The high-resolution mass spectrum of the corrosion resistant agent prepared in Example 1 is shown.

[0020] Figure 3 The image shows the proton NMR spectrum of the anti-aging agent prepared in Example 4.

[0021] Figure 4 The image shows a high-resolution mass spectrum of the anti-aging agent prepared in Example 4. Detailed Implementation

[0022] The following description, in conjunction with specific embodiments, provides further details, but the present invention is not limited to these embodiments.

[0023] Example 1: Preparation of Corrosion Resistance Agent S1: Under nitrogen protection, 250 ml of acetonitrile, 0.1 mol of 1,3-benzothiazol-5-amine, and 0.201 mol of diethyl 2,3-epoxypropylphosphonate were stirred and mixed. 0.02 mol of triethylamine was added, and the mixture was heated to 60 °C and reacted for 10 h. After cooling to room temperature, the mixture was filtered, and the solution was rotary evaporated at 50 °C to constant weight. Purification was performed using silica gel column chromatography (V... 石油醚 :V 乙酸乙酯 The ratio of intermediate to 1:1 was 2:1, which was then evaporated at 40℃ to constant weight to obtain intermediate 1. Its 1H NMR data are as follows: 1 H NMR (400 MHz, Chloroform-d) δ 9.29 (s, 1H), 7.78 (d, J = 4.6 Hz, 1H), 7.20 (s, 1H), 6.94 (d, J = 4.5 Hz, 1H), 4.21 (d, J = 4.9Hz, 2H), HRMS (m / z):539.1671[M+H] + ; S2: Under nitrogen protection, 500 ml of tetrahydrofuran and 0.205 mol of 2-imidazolidineone-4-carboxylic acid were stirred and mixed. Then, 0.22 mol of dicyclohexylcarbodiimide and 0.02 mol of 4-dimethylaminopyridine were added, and the mixture was stirred for 15 min. 0.1 mol of intermediate 1 was added, and the reaction was carried out at 25 °C for 18 h. After filtration, the mixture was rotary evaporated at 40 °C to constant weight. The final weight was determined using 300 ml of a mixed solution of dichloromethane and methanol (V...). 二氯甲烷 :V 甲醇 =7:3) recrystallized, filtered, and vacuum dried at 50℃ for 12 h to obtain the corrosion resistant agent; its proton NMR spectrum is as follows. Figure 1 As shown, the proton NMR data are as follows: 1H NMR (400 MHz, DMSO-d6) δ 9.28 (s, 1H), 7.96 (d, J = 3.5 Hz, 2H), 7.78 (d, J = 5.7 Hz, 1H), 7.60 (d, J = 3.6 Hz, 2H), 7.23 (s, 1H), 7.07 (d, J= 5.5 Hz, 1H), 4.87 (d, J = 1.0 Hz, 2H), 4.48 (d, J = 1.2 Hz, 2H), 4.11-3.98(m, 8H), 3.57-3.21 (m, 8H), 2.67 (d, J = 2.3 Hz, 4H), 1.27 (t, J = 6.3 Its high-resolution mass spectrum is as follows: (Hz, 12H); Figure 2 The mass spectrometry data are as follows: HRMS (m / z): 763.2215 [M+H] + .

[0024] Example 2 Preparation of corrosion resistance agent S1: Under nitrogen protection, 250 ml of acetonitrile, 0.1 mol of 1,3-benzothiazol-5-amine, and 0.202 mol of diethyl 2,3-epoxypropylphosphonate were stirred and mixed. 0.02 mol of triethylamine was added, and the mixture was heated to 65 °C and reacted for 9 h. After cooling to room temperature, the mixture was filtered, and the solution was rotary evaporated at 50 °C to constant weight. Purification was performed using silica gel column chromatography (V... 石油醚 :V 乙酸乙酯 =2:1→1:1), evaporated at 40℃ to constant weight, and vacuum dried at 50℃ for 8h to obtain intermediate 1; S2: Under nitrogen protection, 500 ml of tetrahydrofuran and 0.208 mol of 2-imidazolidineone-4-carboxylic acid were stirred and mixed. Then, 0.22 mol of dicyclohexylcarbodiimide and 0.02 mol of 4-dimethylaminopyridine were added, and the mixture was stirred for 15 min. 0.1 mol of intermediate 1 was added, and the reaction was carried out at 25 °C for 18 h. After filtration, the mixture was rotary evaporated at 40 °C to constant weight. The final weight was determined using 300 ml of a mixed solution of dichloromethane and methanol (V...). 二氯甲烷 :V 甲醇 =7:3) recrystallize, filter, and vacuum dry at 50℃ for 12h to obtain corrosion resistant agent.

[0025] Example 3 Preparation of corrosion resistant agent S1: Under nitrogen protection, 250 ml of acetonitrile, 0.1 mol of 1,3-benzothiazol-5-amine, and 0.203 mol of diethyl 2,3-epoxypropylphosphonate were stirred and mixed. 0.02 mol of triethylamine was added, and the mixture was heated to 70 °C and reacted for 8 h. After cooling to room temperature, the mixture was filtered, and the solution was rotary evaporated at 50 °C to constant weight. Purification was performed using silica gel column chromatography (V... 石油醚 :V乙酸乙酯 =2:1→1:1), evaporated at 40℃ to constant weight, and vacuum dried at 50℃ for 8h to obtain intermediate 1; S2: Under nitrogen protection, 500 ml of tetrahydrofuran and 0.21 mol of 2-imidazolium-4-carboxylic acid were stirred and mixed. Then, 0.22 mol of dicyclohexylcarbodiimide and 0.02 mol of 4-dimethylaminopyridine were added, and the mixture was stirred for 15 min. 0.1 mol of intermediate 1 was added, and the reaction was carried out at 30 °C for 17 h. The mixture was filtered, and the solution was rotary evaporated at 40 °C to constant weight. The final weight was determined using 300 ml of a mixture of dichloromethane and methanol (V...). 二氯甲烷 :V 甲醇 =7:3) recrystallize, filter, and vacuum dry at 50℃ for 12h to obtain corrosion resistant agent.

[0026] Example 4 Preparation of Anti-aging Agent N1: Under nitrogen protection, 200 ml of acetonitrile and 0.1 mol of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine were stirred and mixed. 0.102 mol of 1,2-epoxydodecane was slowly added dropwise over 20 min. Then, 0.01 mol of triethylamine was added, and the mixture was heated to 70 °C and reacted for 10 h. After cooling to room temperature, the mixture was filtered, and the solution was rotary evaporated at 50 °C to constant weight. 180 ml of cold diethyl ether was added and stirred to precipitate the precipitate. The precipitate was filtered, washed with cold diethyl ether (3 × 30 ml), and dried under vacuum at 50 °C for 12 h to obtain intermediate A. Its 1H NMR data are as follows: 1 H NMR(400 MHz, DMSO-d6) δ 7.81 (s, 1H), 7.29-7.21 (m, 2H), 7.10-6.92 (m, 5H), 6.82-6.74 (m, 2H), 4.62 (d, J = 5.0 Hz, 1H), 3.64 (d, J = 5.0 Hz, 1H), 3.60(d, J = 1.0 Hz, 1H), 3.20-2.92 (m, 2H), 1.56 (d, J = 12.4 Hz, 1H), 1.50-1.24(m, 20H), 1.14 (s, 3H), 0.96-0.87 (m, 9H); HRMS (m / z): 453.3771 [M+H] + ; Under nitrogen protection, 350 ml of tetrahydrofuran, 0.1 mol of tripropylene phosphite, 0.305 mol of 2-(2-mercaptoethyl)-1H-benzimidazole-5-carboxylic acid, and 1.54 g of 2,2-dimethoxy-2-phenylacetophenone were stirred and mixed thoroughly at room temperature under an intensity of 20 mW / cm². 2Irradiated with 365 nm ultraviolet light for 40 min, rotary evaporated at 40 °C to constant weight, added 300 ml of cold n-hexane and stirred to precipitate, filtered, the filter cake was washed with 80 ml of cold n-hexane and dried under vacuum at 40 °C for 12 h to obtain intermediate B; its 1H NMR data are as follows: 1 H NMR (400 MHz, DMSO-d6) δ 12.43 (s, 3H), 11.21 (s, 3H), 8.21 (d, J =3.5 Hz, 3H), 7.95 (s, 3H), 7.59 (d, J = 3.5 Hz, 3H), 3.69-3.60 (m, 6H), 3.25-3.18 (m, 6H), 2.85-2.78 (m, 6H), 2.75-2.70 (m, 6H), 1.83-1.75 (m, 6H); HRMS(m / z):869.2153[M+H] + ; Under nitrogen protection, 1000 ml of tetrahydrofuran, 0.1 mol of intermediate B, 0.32 mol of dicyclohexylcarbodiimide, and 0.03 mol of 4-dimethylaminopyridine were stirred and mixed. Then, 0.31 mol of intermediate A was added, and the mixture was reacted at 25 °C for 18 h. After filtration, the mixture was rotary evaporated at 40 °C to constant weight. The crude product was purified by silica gel column chromatography (V... 石油醚 :V 乙酸乙酯 =1:2), evaporated at 40℃ to constant weight, to obtain the anti-aging agent; its proton NMR spectrum is as follows. Figure 3 As shown, the proton NMR data are as follows: 1H NMR (400 MHz, DMSO-d6) δ 12.44 (s,3H), 8.31 (d, J = 4.5 Hz, 3H), 7.99 (d, J = 3.5 Hz, 3H), 7.80 (s, 3H), 7.63(d, J = 4.1 Hz, 3H), 7.30-7.20 (m, 6H), 7.09-6.93 (m, 15H), 6.81-6.74 (m,6H), 5.03-4.86 (m, 3H), 3.71-3.58 (m, 6H), 3.53 (d, J = 1.0 Hz, 3H), 3.46 (d,J = 12.4 Hz, 2H), 3.24 (d,J = 12.4 Hz, 10H), 2.87–2.66 (m, 12H), 1.93–1.75 (m, 12H), 1.49 (d, J = 12.4 Hz, 3H), 1.43–1.25 (m, 54H), 1.15 (s, 9H), 0.97–0.87 (m, 27H); its high-resolution mass spectrum is shown below. Figure 4 As shown, the mass spectrometry data are as follows: HRMS (m / z): 2173.3168 [M+H] + .

[0027] Example 5: Preparation of a self-cleaning coating with high hardness, anti-aging, and corrosion resistance (1) Weigh the following by weight: 25g epoxy resin, 20g polyurethane resin, 8g fluorocarbon resin, 2g nano zirconium oxide, 1g nano silica, 3g nano titanium dioxide, 0.5g hydrophobic fumed silica, 1g corrosion resistant agent (prepared in Example 1), 1g anti-aging agent (prepared in Example 4), 0.5g leveling agent (Efka® FL 3680), 0.5g dispersant (BYK-163), 10g curing agent, and 40g organic solvent (28g xylene, 12g butyl acetate); (2) Add organic solvent, nano-zirconia and nano-silica to a high-speed disperser and disperse at 2000 rpm for 45 min. Then add nano-titanium dioxide and hydrophobic fumed silica and continue to disperse for 45 min to obtain a slurry. Transfer the slurry to a sand mill and grind it for 3 h with zirconia beads with a diameter of 0.8 mm. Control the particle size D90 < 50 nm to obtain a pre-dispersed filler system. Add epoxy resin, polyurethane resin and fluorocarbon resin to a reaction vessel, heat to 70℃, stir and mix at 600 rpm for 45 min. Then add corrosion resistant agent, anti-aging agent, leveling agent, dispersant and pre-dispersed filler system in sequence, stir and mix at 1200 rpm for 90 min, cool to 40℃, add curing agent, stir at 400 rpm for 60 min, pass through a 200 mesh sieve, and cure at 25℃ for 36 h to obtain a high-hardness, anti-aging and anti-corrosion self-cleaning coating.

[0028] Example 6: Preparation of a self-cleaning coating with high hardness, anti-aging, and corrosion resistance (1) Weigh the following by weight: 35g epoxy resin, 25g polyurethane resin, 12g fluorocarbon resin, 2.5g nano zirconium oxide, 1.5g nano silica, 4g nano titanium dioxide, 1.2g hydrophobic fumed silica, 1.5g corrosion resistant agent (prepared in Example 2), 2g anti-aging agent (prepared in Example 4), 1.5g leveling agent (Efka® FL 3680), 1.3g dispersant (BYK-163), 12g curing agent, and 50g organic solvent (35g xylene, 15g butyl acetate); (2) Add organic solvent, nano-zirconia and nano-silica to a high-speed disperser and disperse at 2000 rpm for 45 min. Then add nano-titanium dioxide and hydrophobic fumed silica and continue to disperse for 45 min to obtain a slurry. Transfer the slurry to a sand mill and grind it for 3 h with zirconia beads with a diameter of 0.8 mm. Control the particle size D90 < 50 nm to obtain a pre-dispersed filler system. Add epoxy resin, polyurethane resin and fluorocarbon resin to a reaction vessel, heat to 70℃, stir and mix at 600 rpm for 45 min. Then add corrosion resistant agent, anti-aging agent, leveling agent, dispersant and pre-dispersed filler system in sequence, stir and mix at 1200 rpm for 90 min, cool to 40℃, add curing agent, stir at 400 rpm for 60 min, pass through a 200 mesh sieve, and cure at 25℃ for 36 h to obtain a high-hardness, anti-aging and anti-corrosion self-cleaning coating.

[0029] Example 7: Preparation of a self-cleaning coating with high hardness, anti-aging, and corrosion resistance (1) Weigh the following by weight: 40g epoxy resin, 30g polyurethane resin, 15g fluorocarbon resin, 3g nano zirconium oxide, 2g nano silica, 5g nano titanium dioxide, 2g hydrophobic fumed silica, 2g corrosion resistant agent (prepared in Example 3), 3g anti-aging agent (prepared in Example 4), 2g leveling agent (Efka® FL 3680), 2g dispersant (BYK-163), 15g curing agent, and 60g organic solvent (42g xylene, 18g butyl acetate); (2) Add organic solvent, nano-zirconia and nano-silica to a high-speed disperser and disperse at 2000 rpm for 45 min. Then add nano-titanium dioxide and hydrophobic fumed silica and continue to disperse for 45 min to obtain a slurry. Transfer the slurry to a sand mill and grind it for 3 h with zirconia beads with a diameter of 0.8 mm. Control the particle size D90 < 50 nm to obtain a pre-dispersed filler system. Add epoxy resin, polyurethane resin and fluorocarbon resin to a reaction vessel, heat to 70℃, stir and mix at 600 rpm for 45 min. Then add corrosion resistant agent, anti-aging agent, leveling agent, dispersant and pre-dispersed filler system in sequence, stir and mix at 1200 rpm for 90 min, cool to 40℃, add curing agent, stir at 400 rpm for 60 min, pass through a 200 mesh sieve, and cure at 25℃ for 36 h to obtain a high-hardness, anti-aging and anti-corrosion self-cleaning coating.

[0030] Comparative Example 1 The raw material composition and preparation method of the high-hardness, anti-aging, and anti-corrosion self-cleaning coating are basically the same as those in Example 6, except that the corrosion resistant agent is replaced with an equal weight of corrosion resistant agent prepared by the following method: The preparation method of the corrosion resistant agent is basically the same as that in Example 2, except that the 1,3-benzothiazole-5-amine in step S1 is replaced with an equimolar amount of 5-aminobenzothiophene.

[0031] Comparative Example 2 The raw material composition and preparation method of the high-hardness, anti-aging, and anti-corrosion self-cleaning coating are basically the same as those in Example 6, except that the corrosion resistant agent is replaced with an equal weight of corrosion resistant agent prepared by the following method: The preparation method of the corrosion resistant agent is basically the same as that in Example 2, except that the amount of 2,3-epoxypropylphosphonic acid diethyl ester in step S1 is replaced with 0.101 mol; the amount of 2-imidazolidineone-4-carboxylic acid in step S2 is replaced with 0.105 mol, the amount of dicyclohexylcarbodiimide is replaced with 0.11 mol, and the amount of 4-dimethylaminopyridine is replaced with 0.01 mol.

[0032] Comparative Example 3 The raw material composition and preparation method of the high-hardness, anti-aging, and anti-corrosion self-cleaning coating are basically the same as those in Example 6, except that the corrosion resistant agent is replaced with an equal weight of corrosion resistant agent prepared by the following method: The preparation method of the corrosion resistant agent is basically the same as that in Example 2, except that the 2-imidazolidineone-4-carboxylic acid in step S2 is replaced with an equimolar amount of 1H-imidazol-4-carboxylic acid.

[0033] Comparative Example 4 The raw material composition and preparation method of the high-hardness, anti-aging, and anti-corrosion self-cleaning coating are basically the same as those in Example 6, except that the anti-aging agent is replaced with an equal weight of an anti-aging agent prepared by the following method: The preparation method of the anti-aging agent is basically the same as that in Example 4, except that N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine in step N1 is replaced with an equimolar amount of 4-benzyl-N-isopropylaniline (CAS No. 1153938-91-0).

[0034] Comparative Example 5 The raw material composition and preparation method of the high-hardness, anti-aging, and anti-corrosion self-cleaning coating are basically the same as those in Example 6, except that the anti-aging agent is replaced with an equal weight of an anti-aging agent prepared by the following method: The preparation method of the anti-aging agent is basically the same as that in Example 4, except that 1,2-epoxydodecane in step N1 is replaced with an equimolar amount of 1,2-epoxyhexane.

[0035] Comparative Example 6 The raw material composition and preparation method of the high-hardness, anti-aging, and anti-corrosion self-cleaning coating are basically the same as those in Example 6, except that the anti-aging agent is replaced with an equal weight of an anti-aging agent prepared by the following method: The preparation method of the anti-aging agent is basically the same as that in Example 4, except that 2-(2-mercaptoethyl)-1H-benzimidazole-5-carboxylic acid in step N2 is replaced with an equimolar amount of 4-(2-mercaptoethyl)benzoic acid (CAS No. 930102-58-2).

[0036] Comparative Example 7 The raw material composition and preparation method of the high-hardness, anti-aging, and anti-corrosion self-cleaning coating are basically the same as those in Example 6, except that the anti-aging agent is replaced with an equal weight of an anti-aging agent prepared by the following method: The preparation method of the anti-aging agent is basically the same as that in Example 4, except that the amount of intermediate A in step N3 is replaced with 0.21 mol, the amount of dicyclohexylcarbodiimide is replaced with 0.22 mol, and the amount of 4-dimethylaminopyridine is replaced with 0.02 mol.

[0037] The epoxy resin used in the embodiments and comparative examples of this application is bisphenol A type epoxy resin E-44, produced by Shandong Deyuan Epoxy Technology Co., Ltd.; the polyurethane resin is aliphatic polyurethane acrylate, model B-6210, produced by Guangdong Boxin New Material Technology Co., Ltd.; the fluorocarbon resin is model HLR-P, produced by Shandong Huafu Chemical Co., Ltd.; the nano-zirconia is model JA-TAP-0, produced by Shandong Shengtai Zirconium Resources Co., Ltd.; the nano-silica is model UG-SP30S, produced by Suzhou Youzirconium Nanomaterials Co., Ltd.; the nano-titanium dioxide is anatase nano-titanium dioxide, model JWN-TO-A10M, produced by Ningbo Jiwei Nanomaterials Technology Co., Ltd.; the hydrophobic fumed silica is Degussa R972 hydrophobic fumed silica; and the curing agent is aliphatic polyisocyanate curing agent, model Desmodur® N. 3800, produced by Shanghai Panbiao Materials Science and Technology Co., Ltd.; the CAS number of 2-(2-mercaptoethyl)-1H-benzimidazole-5-carboxylic acid is 838837-37-9.

[0038] The performance of the self-cleaning coatings prepared in Examples 5-7 and Comparative Examples 1-7 was tested, and the test results are shown in Table 1.

[0039] Sample preparation: Tinplate was used as the substrate. The tinplate met the technical requirements of GB / T 9271 and had a size of 150mm×70mm×4mm. The coatings prepared in Examples 5-7 and Comparative Examples 1-7 were uniformly applied to the surface of the tinplate using an SZQ-100 coating preparation device. The coating thickness was 100μm. The prepared samples were placed in a forced-air drying oven and dried at 180℃ for 24h. The temperature was then lowered to 23℃ and placed at 50% relative humidity for 24h to obtain the samples. The samples were then tested for hardness, anti-aging, corrosion resistance and self-cleaning performance.

[0040] Hardness test: Refer to GB / T 6739-2006 standard and use 101 Zhonghua brand drawing pencil to test the hardness of the sample.

[0041] Anti-aging performance test: The sample was placed in a QUV accelerated aging test chamber for aging test, with an irradiation wavelength of 310nm and an irradiation intensity of 0.89W / m. 2 The temperature was 60℃ and the aging time was 800h. The hardness of the aged sample was tested again.

[0042] Corrosion resistance test: The samples were subjected to salt spray testing in a JST-120 salt spray chamber. The test temperature was 35℃, the corrosive medium was a 5wt% NaCl solution, the spray method was continuous spraying, and the salt spray deposition rate was 1ml / 80cm. 2• h, test time 2000h, observe the condition of the sample surface after the test.

[0043] Self-cleaning performance test: (1) Contact angle test: 1 μL of deionized water was dropped onto the sample surface. The static water contact angle and roll-off angle were measured using a contact angle measuring instrument at a temperature of 23℃ and a relative humidity of 50%.

[0044] (2) Stain resistance test: The stain resistance test of the sample was carried out by the brushing method in GB / T 9780-2013 standard, and the rate of decrease in the reflectance coefficient of the sample was calculated.

[0045] Table 1 Performance Test Data

[0046] As can be seen from Table 1, the self-cleaning coatings prepared in Examples 5-7 of this application have high hardness and excellent anti-aging, corrosion resistance and self-cleaning properties.

[0047] The corrosion resistant agent added to the self-cleaning coating prepared in this application is a multifunctional organic molecule that simultaneously incorporates phosphate ester, benzothiazole, and imidazolidinone structures. The phosphate ester group can coordinate and chemically adsorb metal ions on the surface of the metal substrate, forming a stable phosphorus-oxygen bonded layer and a dense passivation film at the interface, inhibiting the anodic dissolution process of the metal. The nitrogen, sulfur atoms, and aromatic ring π-electron system in the benzothiazole structure can form complexes with metal ions, enhancing the stability of the adsorption film and inhibiting the cathodic reaction. The imidazolidinone structure provides multiple coordination sites between the carbonyl group and nitrogen atoms, further improving the metal ion complexation ability, and can also form hydrogen bonds with the resin matrix, improving the dispersion stability and interfacial anchoring ability of the corrosion resistant agent in the coating. The synergistic effect of the various functional groups in the corrosion resistant agent molecule constructs a dense and stable chemically adsorbed protective layer on the metal surface, and forms a physical shielding synergistic protection system with the highly cross-linked network and nanofillers of the coating, effectively blocking the penetration of moisture, oxygen, and corrosive media, thereby significantly improving the corrosion resistance of the coating. The corrosion inhibitor used in Comparative Example 1 lacks the nitrogen atom in the benzothiazole structure, which weakens its ability to complex with metal ions and reduces the corrosion resistance of the coating. The corrosion inhibitor used in Comparative Example 3 lacks a carbonyl group on the imidazole ring, which weakens both its ability to complex with metal ions and its ability to form hydrogen bonds with the resin matrix. This weakens the interfacial anchoring ability of the corrosion inhibitor in the coating and reduces the corrosion resistance of the coating.

[0048] The anti-aging agent added to the self-cleaning coating prepared in this application has a three-arm structure with a triphosphite core, and each arm simultaneously introduces a thioether bond, a benzimidazole structure, a hindered amine group, and a long flexible alkyl chain. Among these components, the phosphite triester group can decompose the hydroperoxides generated during coating aging, blocking the oxidation chain reaction; the thioether bond further reacts with peroxy free radicals, synergistically improving the antioxidant efficiency; the benzimidazole structure has excellent UV absorption capacity and can complex trace metal ions, reducing the catalytic effect of metal ions on the oxidation reaction; the hindered amine group continuously removes active free radicals generated during photo-oxidation through a free radical capture and regeneration cycle mechanism, achieving long-term photostability; the long flexible alkyl chain improves the compatibility and dispersion stability of the anti-aging agent in the resin system, preventing migration and precipitation. Simultaneously, the long flexible alkyl chain has significant hydrophobic properties, tending to align on the surface during coating curing and film formation, reducing the surface free energy of the coating, and decreasing the wetting and adhesion of moisture and contaminants on the surface, thereby enhancing the self-cleaning performance of the coating; furthermore, the rigid aromatic ring and multi-arm structure in the molecule have a certain restrictive effect on the movement of micro-chain segments in the system, helping to maintain the high hardness and mechanical stability of the coating. The synergistic effect of the various functional groups in the anti-aging agent molecule forms multiple stable protective mechanisms within the coating, effectively improving the anti-aging performance of the coating. The anti-aging agent used in Comparative Example 4 lacks hindered amine groups, which weakens its ability to scavenge active free radicals and reduces its synergistic effect with other functional groups in the molecule, resulting in a decrease in the anti-aging performance of the coating. The anti-aging agent used in Comparative Example 7 contains only two molecules of hindered amine groups and a long flexible alkyl chain, which weakens its ability to scavenge active free radicals and reduces its dispersibility in the resin system. At the same time, the rigid aromatic ring structure is reduced, resulting in a decrease in both the anti-aging performance and hardness of the coating.

[0049] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.

Claims

1. A self-cleaning coating with high hardness, anti-aging, and corrosion resistance, characterized in that, The ingredients include the following parts by weight: Epoxy resin 25-40 parts, polyurethane resin 20-30 parts, fluorocarbon resin 8-15 parts, nano zirconium oxide 2-3 parts, nano silica 1-2 parts, nano titanium dioxide 3-5 parts, hydrophobic fumed silica 0.5-2 parts, corrosion resistant agent 1-2 parts, anti-aging agent 1-3 parts, leveling agent 0.5-2 parts, dispersant 0.5-2 parts, curing agent 10-15 parts, organic solvent 40-60 parts; The chemical structural formula of the corrosion resistant agent is as follows: ; The chemical structural formula of the anti-aging agent is as follows: 。 2. The self-cleaning coating with high hardness, anti-aging, and corrosion resistance according to claim 1, characterized in that, The corrosion resistant agent is prepared by the following method: S1: 1,3-Benzothiazole-5-amine reacts with diethyl 2,3-epoxypropylphosphonate to generate intermediate 1. S2: Intermediate 1 reacts with 2-imidazolidineone-4-carboxylic acid to generate a corrosion resistant agent.

3. The self-cleaning coating with high hardness, anti-aging, and corrosion resistance according to claim 2, characterized in that, In step S1, the molar ratio of 1,3-benzothiazole-5-amine to diethyl 2,3-epoxypropylphosphonate is 1:(2.01-2.03).

4. The self-cleaning coating with high hardness, anti-aging, and corrosion resistance according to claim 2, characterized in that, In step S2, the molar ratio of intermediate 1 to 2-imidazolidineone-4-carboxylic acid is 1:(2.05-2.1).

5. The self-cleaning coating with high hardness, anti-aging, and corrosion resistance according to claim 1, characterized in that, The anti-aging agent is prepared by the following method: N1: N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine reacts with 1,2-epoxydodecane to generate intermediate A. N2: Tripropylene phosphite reacts with 2-(2-mercaptoethyl)-1H-benzimidazole-5-carboxylic acid to generate intermediate B. N3: Intermediate B reacts with intermediate A to generate an anti-aging agent.

6. The self-cleaning coating with high hardness, anti-aging, and corrosion resistance according to claim 5, characterized in that, In step N1, the molar ratio of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine to 1,2-epoxydodecane is 1:1.

02.

7. The self-cleaning coating with high hardness, anti-aging, and corrosion resistance according to claim 5, characterized in that, In step N2, the molar ratio of tripropylene phosphite to 2-(2-mercaptoethyl)-1H-benzimidazole-5-carboxylic acid is 1:3.

05.

8. The self-cleaning coating with high hardness, anti-aging, and corrosion resistance according to claim 5, characterized in that, In step N3, the molar ratio of intermediate B to intermediate A is 1:3.

1.

9. The self-cleaning coating with high hardness, anti-aging, and corrosion resistance according to claim 1, characterized in that, The organic solvent is a mixed solution of xylene and butyl acetate.

10. A method for preparing a high-hardness, anti-aging, and corrosion-resistant self-cleaning coating as described in any one of claims 1-9, characterized in that, Includes the following steps: (1) Weigh the following by weight: 25-40 parts epoxy resin, 20-30 parts polyurethane resin, 8-15 parts fluorocarbon resin, 2-3 parts nano zirconium oxide, 1-2 parts nano silica, 3-5 parts nano titanium dioxide, 0.5-2 parts hydrophobic fumed silica, 1-2 parts corrosion resistant agent, 1-3 parts anti-aging agent, 0.5-2 parts leveling agent, 0.5-2 parts dispersant, 10-15 parts curing agent, and 40-60 parts organic solvent; (2) Disperse organic solvent, nano zirconium oxide and nano silica evenly, add nano titanium dioxide and hydrophobic fumed silica, continue to disperse evenly to obtain slurry, grind the slurry to obtain pre-dispersed filler system; mix epoxy resin, polyurethane resin and fluorocarbon resin, heat and stir, then add corrosion resistant agent, anti-aging agent, leveling agent, dispersant and pre-dispersed filler system in sequence, stir and mix evenly, cool down, add curing agent, stir, sieve and mature to obtain high hardness, anti-aging and anti-corrosion self-cleaning coating.

Citation Information

Patent Citations

  • Pt-TiO2-SiO2 photocatalytic self-cleaning composite material and preparation method thereof

    CN109608913A